Entrepreneurial stories, narratives and reading – Their role in building entrepreneurial being and behaviour. (August 2020) - Manning, Paul; Stokes, Peter; Tarba, Shlomo Yedidia; Rodgers, Peter
The article undertakes an innovative study focusing on the choices and manners of entrepreneur reading as a means of developing resilience and responding to the challenges and crises that entrepreneurial activity presents. The article explores predominant patterns of entrepreneurial learning and challenges the assumptions on which these are grounded. This allows original insights and perspectives to be developed with which to enhance understanding of entrepreneurial sense-making. The study employs a qualitative methodology involving purposive semi-structured interviews with entrepreneurs to determine the ways in which they identify, engage with and operationalize entrepreneurial behaviour based on their reading. The ensuing fieldwork provided a range of findings and discussion themes centred on dynamic and non-linear behaviour, reading and transformative learning events, and social interaction and reading. The study concludes with a range of observations on the power of reading in assisting entrepreneurs to develop resilience and behaviours for coping with the challenges and crises which are an integral aspect of entrepreneurial activity.